IMPROVING WRITING DRAMA SCRIPT SKILLS USING VIDEO AS MEDIA ON YOUTUBE CHANNEL FOR CLASS VIII STUDENTS OF SMPN 1 SARADAN - Dhony Franciska; Dwi Rohman Soleh; Nunung Nurhidayati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Writing is one of the skills that students must learn in text-based learning in Indonesian learning subjects. Writing drama scripts is one of the writing skills that must be learned by junior high school students, which is one of the competencies contained in Indonesian subjects that must be achieved by students. Therefore, it is important for teachers to apply appropriate learning media in accordance with current technological developments so that teachers and students can achieve the learning objectives. Youtube can be used as a learning medium to improve writing drama script skills for class VIII junior high school students. Type of the research is Classroom Action Research. The collected data are analyzed using quantitative methods and described in a descriptive way. The results indicate that through YouTube, the writing skills of Class VIII students of SMPN 1 Saradan can be improved. It can be seen from the pre-cycle where the number of students' achievement in writing drama scripts was 53.5%, in cycle 1 was 75%, and in cycle 2 was 92.8%. It implies that YouTube is highly effective to increase students' interest and writing skills. Apart from that, YouTube can also help educators to explain the learning materials for students that cannot be described directly.